(untitled) (Web of Teachers: Inderscience Research, 2025)
The article examines the risks arising at cotton ginning and textile plants, fuel and lubricant warehouses, as well as in oil and petroleum product storage facilities. This solves the problem of increasing the heat resistance and fire resistance of structures, and also reduces the force of a strong shock wave, hydrodynamic flow wave, flame and high pressure generated during an explosion.